Affirmation and Expansion of the Object and Subject of Disputes Between Election Participants in the Electoral Process - Putri Sondi (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
General Elections (Pemilu) serve as a fundamental pillar of modern democratic systems, acting as a primary means for the realization of popular sovereignty. Through elections, citizens are given the opportunity to directly shape the political direction and leadership of the country. However, in practice, elections in Indonesia are often accompanied by various issues, including disputes—not only between participants and election organizers, but also among the participants themselves. Law Number 7 of 2017 concerning General Elections provides clear regulation only for disputes involving decisions made by the General Elections Commission (KPU), yet it fails to explicitly address conflicts between political contestants. This regulatory gap results in a vacuum of norm and leads to legal uncertainty on the ground. This study aims to identify who qualifies as the legal subjects and what constitutes the legal objects in disputes between election participants. It also seeks to determine the appropriate legal classification for resolving such disputes: whether they fall under public law or are more suitably handled as matters of private law. Using a normative legal approach—grounded in legal literature and legislative analysis—and a conceptual approach to explore ideal dispute resolution structures within the Indonesian legal framework, this study provides a comprehensive theoretical and normative mapping. The findings suggest that disputes between election participants should be situated within the realm of private law, particularly civil law, since they usually concern unlawful acts committed between equal parties, such as political defamation, breaches of campaign agreements, or reputational damage. This is consistent with the views of Sudikno Mertokusumo, who argued that civil law governs relationships between parties on an equal footing and does not involve direct public authority. Therefore, electoral regulatory reform is needed to ensure legal certainty and provide a fair dispute resolution mechanism, ultimately strengthening democratic legitimacy and promoting ethical political competition